2019
DOI: 10.1002/acp.3536
|View full text |Cite
|
Sign up to set email alerts
|

Using the model statement to elicit verbal differences between truth tellers and liars amongst Arab interviewees: A partial replication of Leal, Vrij, Deeb, and Jupe (2018)

Abstract: Leal, Vrij, Deeb and Jupe (2018) found -with British participants-that a Model Statement elicited (1) more information and (2) a cue to deceit: After exposure to a Model Statement liars reported significantly more peripheral information than truth tellers. We sought to replicate these findings with Arabs living in Israel. Truth tellers and liars reported a stand-out event that they had (truth tellers) or pretended to have (liars) experienced in the last two

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In the 14 published MS studies that we are interested in, information elicitation effects were observed (Bogaard, Meijer, & Vrij, 2014; Bogaard et al, 2020; Ewens et al, 2016; Harvey, Vrij, Leal, Lafferty, & Nahari, 2017; Harvey, Vrij, Leal, Hope, & Mann, 2019; Kleinberg, Van Der Toolen, Vrij, Arntz, & Verschuere, 2018; Leal et al, 2015; Leal, Vrij, Deeb, & Jupe, 2018; Leal, et al, 2019b; Porter et al, 2018, Porter & Salvanelli, 2020; Vrij et al, 2017a; Vrij, Leal, Jupe, & Harvey, 2018; Vrij et al, 2020). However, in general, a review of the literature reveals that the MS has been (largely) unsuccessful at enhancing lie‐detection performance (see Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the 14 published MS studies that we are interested in, information elicitation effects were observed (Bogaard, Meijer, & Vrij, 2014; Bogaard et al, 2020; Ewens et al, 2016; Harvey, Vrij, Leal, Lafferty, & Nahari, 2017; Harvey, Vrij, Leal, Hope, & Mann, 2019; Kleinberg, Van Der Toolen, Vrij, Arntz, & Verschuere, 2018; Leal et al, 2015; Leal, Vrij, Deeb, & Jupe, 2018; Leal, et al, 2019b; Porter et al, 2018, Porter & Salvanelli, 2020; Vrij et al, 2017a; Vrij, Leal, Jupe, & Harvey, 2018; Vrij et al, 2020). However, in general, a review of the literature reveals that the MS has been (largely) unsuccessful at enhancing lie‐detection performance (see Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Leal and colleagues (2018, 2019b) made a distinction between core and peripheral detail reported by interviewees after hearing a MS. Core details include information about the main event, whereas peripheral details include information that is irrelevant to the main event.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations